Melanoma care during one year pandemic in Berlin: decreasing appointment cancellations despite increasing COVID-19 concern - Micek, Aleksandra; Diehl, Katharina; Teuscher, Miriam; Schaarschmidt, Marthe-Lisa; Sasama, Bianca; Ohletz, Jan; Burbach, Guido; Kiecker, Felix; Hillen, Uwe; Harth, Wolfgang; Peitsch, Wiebke K. (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Background and objectives: The COVID-19 pandemic poses a great challenge for cancer patients. Our aim was to assess its influence on treatment and appointments of melanoma patients after one year of pandemic. Methods: Melanoma patients treated in the Vivantes Skin Cancer Centre in Berlin, Germany completed a postal survey on pandemic-related alterations in melanoma care. Impact factors on changes of appointments were examined with descriptive analyses and multivariate logistic regression. Data after one year of pandemic were compared to those after its first wave. Results: Among 366 participants (57.7 % males; mean age 69.2 years, response rate: 36.1 %), 38 (10.1 %) reported postponed or missed appointments, mostly on their own demand (71.1 %) due to fear of COVID-19 (52.6 %). Current treatment was associated with a lower risk of changing appointments (Odds Ratio [OR]: 0.194, p = 0.002), higher age (OR: 1.037, p = 0.039), longer disease duration (OR: 1.007, p = 0.028), and higher school degree (OR: 2.263, p = 0.043) with higher probability. Among 177 patients currently receiving therapy, only 1.7 % experienced pandemic-related treatment alterations. Concern about COVID-19 was significantly higher after one year of pandemic than after its first wave, but the number of missed appointments was lower. Conclusions: Pandemic-related changes were rare in our cohort and decreased over time despite increasing concern.
CRIS-Team Scopus Importer:2022-06-17